Effect of patient‐centered transitional care services on patient‐reported outcomes in heart failure: sex‐specific analysis of the PACT‐HF randomized controlled trial. (16th August 2021) - Blumer, Vanessa; Gayowsky, Anastasia; Xie, Feng; Greene, Stephen J.; Graham, Michelle M.; Ezekowitz, Justin A.; Perez, Richard; Ko, Dennis T.; Thabane, Lehana; Zannad, Faiez; Van Spall, Harriette G.C.
Abstract : Aims: We assessed the effect of transitional care on patient‐reported outcomes (PROs) in women and men hospitalized for heart failure. Methods and results: In this sex‐specific analysis of a stepped wedge cluster randomized trial in Canada, the effect of a patient‐centered transitional care model was tested on pre‐specified PROs of discharge preparedness (B‐PREPARED score, range 0–22), quality of transition [Care Transitions Measure‐3 (CTM‐3) score, range 0–100], and health‐related quality of life (HRQOL) (EQ‐5D‐5L, range 0–1). Among 986 patients (47.4% women), B‐PREPARED at 6 weeks was greater with the intervention than usual care [mean difference (MD) 4.01 (95% confidence interval‐CI 2.90–5.12); P  < 0.001], with no sex differences ( P sex‐interaction = 0.24). CTM‐3 at 6 weeks was greater with the intervention than usual care [MD 10.52 (95% CI 6.00–15.04); P  < 0.001], with no sex differences ( P sex‐interaction = 0.69). EQ‐5D‐5L was greater with intervention than usual care at discharge [MD 0.17 (95% CI 0.12–0.22); P  < 0.001], 6 weeks [MD 0.06 (95% CI 0.01–0.12); P  = 0.02], and 6 months [MD 0.05 (95% CI −0.01 to 0.12); P  = 0.09], although the 6‐month difference was not statistically significant. At discharge, women reported lower EQ‐5D‐5L but experienced significantly greater treatment benefit than men ( P sex‐interaction = 0.02). Treatment effect on EQ‐5D‐5L was numerically greater in women than men at 6 weeks and 6 months, but there were no significant sex differences ( P sex‐interaction 0.18 and 0.19, respectively). Conclusion: A patient‐centered transitional care model improved discharge preparedness, transition quality, and HRQOL in the weeks following heart failure hospitalization, with effects largely consistent in women and men. However, women reported lower HRQOL and experienced greater treatment benefit in this endpoint than men at hospital discharge. Clinical Trial Registration: ClinicalTrials.gov NCT02112227. Abstract : In this sex‐specific analysis of a stepped wedge cluster randomized trial in Canada, a patient‐centered transitional care model improved patient‐reported outcomes (PROs) of discharge preparedness (B‐PREPARED score), quality of transition [Care Transitions Measure‐3 (CTM‐3)], and health‐related quality of life (HRQOL) (EQ‐5D‐5L) in the weeks following heart failure hospitalization, with effects largely consistent in women and men. However, women reported lower HRQOL than men at hospital discharge and experienced greater improvement in HRQOL with the intervention than did men.